2019
DOI: 10.1039/c8fd00210j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast transient absorption spectroscopy of doped P3HT films: distinguishing free and trapped polarons

Abstract: It is generally presumed that the vast majority of carriers created by chemical doping of semiconducting polymer films are coulombically trapped by the counteranion, with only a small fraction that are free and responsible for the increased conductivity essential for organic electronic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 47 publications
7
70
0
Order By: Relevance
“…In most chemically doped conjugated polymers, including PTB7 as shown in the Supporting Information, the new low‐energy optical absorption that results from polarons, labeled P1 in Figure 1a, appears near 0.5 eV (≈2480 nm). [ 30 ] We [ 33,34 ] and others [ 35,36 ] have argued that when the dopant counterion resides close to the polaron on the polymer backbone the polaron can be trapped by the attractive Coulomb interaction, lowering its mobility and blueshifting the absorption of the P1 transition. As shown in Figure 1b, bipolarons are also expected to have an optical transition (BP1) that is higher in energy than that of single polarons.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…In most chemically doped conjugated polymers, including PTB7 as shown in the Supporting Information, the new low‐energy optical absorption that results from polarons, labeled P1 in Figure 1a, appears near 0.5 eV (≈2480 nm). [ 30 ] We [ 33,34 ] and others [ 35,36 ] have argued that when the dopant counterion resides close to the polaron on the polymer backbone the polaron can be trapped by the attractive Coulomb interaction, lowering its mobility and blueshifting the absorption of the P1 transition. As shown in Figure 1b, bipolarons are also expected to have an optical transition (BP1) that is higher in energy than that of single polarons.…”
Section: Figurementioning
confidence: 99%
“…In previous work, we showed that we could distinguish free and Coulombically trapped polarons using ultrafast transient absorption spectroscopy. [ 33 ] The idea behind the experiment is shown in Figure 1a. By exciting the polaron P1 transition, an electron from the valence band is moved to the half‐filled state in the bandgap (left energy level diagram); in essence, the excitation is a photoinduced charge transfer taking an electron from a neutral region of the polymer and filling the hole, thus moving the hole to a new location on the polymer backbone (center diagram).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations